Breastfeeding and its impact on daily life in women with type 1 diabetes during the first six months after childbirth: a prospective cohort study - Berg Marie; Erlandsson Lena-Karin; Sparud-Lundin Carina (BMC, 2012)
Abstract Background For mothers with diabetes, breastfeeding is a great challenge due to their struggle with potentially unstable blood glucose levels. This paper explores breastfeeding attitudes and impact of breastfeeding on the daily life of mothers with type 1 diabetes compared with non-diabetic mothers. Methods We performed a prospective cohort study of 108 mothers with type 1 diabetes and a reference group of 104 mothers in the west of Sweden. Data were collected through medical records and structured telephone interviews at 2 and 6 months after childbirth. Results Women in both the diabetes group and the reference group had high levels of confidence (84% and 93% respectively) in their breastfeeding capacity before childbirth, and 90% assessed breastfeeding as a positive and an important experience during the six months of follow-up. About 80% assessed breastfeeding as influencing daily life 'very much' or 'quite a lot' at 2 months as did 60% at 6 months, with no difference between the groups. In mothers with diabetes, the impact of breastfeeding on the priority of other duties decreased over time, as did feelings of time pressure and negative effects on patterns of sleep. Compared to the reference group, mothers with diabetes at 6 months remained more affected by disruptions in daily life and they felt more worried about their health both at 2 and 6 months after childbirth. For the reference group mothers' sensitivity to unexpected disruptions in daily routines decreased between 2 and 6 months after childbirth, and they expressed a greater need to organize their time than mothers with diabetes. Conclusion Mothers with diabetes type 1 express more worry for own health and are more sensitive to distruptions. To balance their everyday life and to reduce the risk of stress and illhealth they are therefor, compared to other mothers, likely to need additional professional and peer support.